PENGEMBANGAN SISTEM PENGAJUAN UTTP DENGAN MENGGUNAKAN PROGRAM BOOTSTRAP (PHP) DALAM RANGKA PENINGKATAN DAYA SAING DAN INOVASI PADA PT KALIBRASI INDONESIA MANDIRI - Teuku Fadjar Shadek; Shodik Nuryadhin; Ainin Najmi (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
PT Kalibrasi Indonesia Mandiri is one unit of the legal metrology agency in Serang Regency that functions are to control, manage and determine the types of measuring instruments, scales and equipment (UTTP) by setting mass standards, volume standards and length standards. PT Kalibrasi Indonesia Mandiri is under department of Industry, Trade, Cooperatives and SMEs in Banten province, as one of the Technical Implementation Unit (UPT). In accepting UTTP (Measuring, Measure, Weighing, and Equipment) submissions from institutions or companies is still manual and there is no system. For this reasons, the author was designed a system to facilitate the processing of UTTP submissions received at the Technical Implementation Unit in a systemized (online) manner. The solution is using a web-based application. For this reason the author choose the title "Web-based UTTP Submission Information System at PT. Kalibrasi Indonesia Mandiri Serang”. In designing this system the tools used are UML (Unified modeling language) including Flowmaps, Use Case Diagrams, Class Diagrams, Activity Diagrams, Sequence Diagrams, File Structures, Input Output Design. The result of this study is the design of an UTTP submission information system that is used to facilitate work units in maintaining consistency and their level of performance in receiving and preparing test results reports